Salmonella inactivation and cross-contamination on cherry and grape tomatoes under simulated wash conditions. (May 2020) - Bolten, Samantha; Gu, Ganyu; Luo, Yaguang; Van Haute, Sam; Zhou, Bin; Millner, Pat; Micallef, Shirley A.; Nou, Xiangwu
Abstract: Washing in chlorinated water is widely practiced for commercial fresh produce processing. While known as an effective tool for mitigating food safety risks, chlorine washing could also represent an opportunity for spreading microbial contaminations under sub-optimal operating conditions. This study evaluated Salmonella inactivation and cross-contamination in a simulated washing process of cherry and grape tomatoes. Commercially harvested tomatoes and the associated inedible plant matter (debris) were differentially inoculated with kanamycin resistant (KanR) or rifampin resistant (RifR) Salmonella strains, and washed together with uninoculated tomatoes in simulated packinghouse dump tank (flume) wash water. Washing in chlorinated water resulted in significantly higher Salmonella reduction on tomatoes than on debris, achieving 2–3 log reduction on tomatoes and about 1 log reduction on debris. Cross-contamination by Salmonella on tomatoes was significantly reduced in the presence of 25–150 mg/L free chlorine, although sporadic cross-contamination on tomatoes was detected when tomatoes and debris were inoculated at high population density. The majority of the sporadic cross-contaminations originated from Salmonella inoculated on debris. These findings suggested that debris could be a potentially significant source of contamination during commercial tomato washing. Highlights: Salmonella inactivation and cross-contamination during simulated tomato flume washing were examined. Chlorine inactivation of Salmonella on debris was less efficient than on tomato. Sporadic cross-contamination was observed at all free chlorine levels tested, primarily from debris. Debris may be a risk for harboring and disseminating foodborne pathogens in wash water.